Developing a critical influential factors Model (CIFsM) for agile management principles in UAE construction projects - Yamahi, M A; Suratkon, A (2024)
The construction industry plays a crucial role in the global economy, with significant annual expenses and a substantial contribution to the GDP of the UAE. This has led to a surge in building projects, fostering rapid expansion among construction companies. However, challenges have emerged that hinder this growth, including high interest rates and intensified competition among building firms. Additionally, there are many issues impede project timelines and escalate dedicated costs. Many of these challenges can be addressed by addressing inefficiencies within internal processes of companies. Agile construction, a method or approach that facilitates swift adaptation to changes in delivery or design, has the potential to alleviate these challenges. By reducing the time between problem identification and solution implementation, agile construction can enhance project efficiency. This study aims to propose Critical Influential Factors Model (CIFsM) for Agile Management Principles to enhance the performance of construction projects in the UAE. The proposed model covers five critical influential factor groups: organizational, challenges, human resources, technical, and construction industry project performance in the UAE. The research recommends implementing the model empirically using a quantitative approach to enhance integration among construction parties and alleviate concerns about low project performance levels. Developing the CIFsM based on agile management principles offers a promising avenue to enhance construction project performance in the UAE by addressing critical influential factors and adopting an empirical quantitative approach, leading to improved project integration and reduced concerns about low performance levels.